Changes in fractional exhaled nitric oxide, exhaled carbon monoxide and pulmonary function during the acute attack, treatment and remission phases of pediatric asthma - Xie, Zhichao (Transl Pediatr, 2020)
BACKGROUND: The current study aimed to explore the value of fractional exhaled nitric oxide (FeNO), exhaled carbon monoxide (eCO), and pulmonary function in the management of asthmatic children. METHODS: One hundred children diagnosed with asthma were selected as research subjects. Patients were divided into a 3–5-year-old group and a group with children 6 years and older. They were also grouped depending on whether they had asthma alone (A0 group) or whether their asthma was complicated with allergic rhinitis (A+AR group). The FeNO, eCO levels, and pulmonary function in the acute attack period were analyzed 1 month after treatment and clinical remission period. RESULTS: Asthmatic children demonstrated greater pulmonary dysfunction and significantly higher FeNO and eCO during the acute attack phase compared to both one month after treatment and clinical remission. The remission phase was characterized by decreased levels of FeNO and eCO and improvement of pulmonary function. The eCO levels in children aged 3–5 years old, and both FeNO and eCO levels in children 6 years and older were statistically lower during remission regardless of whether the patients had asthma alone or asthma complicated with rhinitis. However, 10% of the 100 children in the clinical remission period still demonstrated mid to high levels of FeNO. The critical value of FeNO levels during the acute period in children 6 years and older with asthma and rhinitis was 34.5 ppb (AUROC 0.814, 95% CI: 0.684–0.944) with a sensitivity of 69.2% and specificity of 93.7%. CONCLUSIONS: Dynamic monitoring of FeNO and eCO is an effective indicator of airway inflammation and thus represents an important clinical tool in assessing the severity of asthma in children.